Pemikiran Pendidikan Hasan Al-Banna - M. Nasihuddin (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2021)
this paper attempts to examine and understand the educational thoughts of Hasan al-Banna who lived in (1906-1949), the founder of the Ikhwan al-Muslimin movement, one of the largest and most influential Islamic organizations of the 20th century. The method used to reveal the results of Hasan's educational thoughts al-Banna is a literature review through materials from books, articles, magazines, or seminar results, and other information related to the issue being studied. Each material or data is analyzed, analyzed, described and concluded inductively, thus this study is descriptive analysis. The results of the study show that the idea of ​​thinking in education is totality and holistic oriented to the divinity, universal, integrated, balanced, and loaded with positive and constructive skills